Perception of the professional self-image by nurses and midwives. Psychometric adaptation of the Belimage questionnaire - Sabina Katarzyna Stadnicka; Danuta Zarzycka (BMC, 2023)
Abstract Background The aim of this paper is to present the research results on the perception of the professional self-image by Polish nurses and midwives as well as the psychometric adaptation of the Belimage scale. Methods A cross-sectional survey was conducted from January to November 2018. The study group consisted of 670 clinical practice nurses and midwives. A diagnostic survey method was applied using the Belimage questionnaire after it obtained acceptable psychometric properties through an adaptation procedure. Results In the group of respondents, the professional image of nurses and midwives is dominated by instrumental skills, documentation and organization of care, and communication skills. There is a statistically significant difference in the image of these two professions in terms of the ability to think and act creatively and critically, as well as innovation and evidence-based practice. The respondents' opinion regarding the perception of their image by themselves and society is statistically significant in each of the analyzed areas. In the professional image created by the public, nurses and midwives recognize that being a nurse/midwife is a vocation-277 (41.3%). However, in terms of their self-image, most nurses and midwives consider their work to be hard-442 (66%) and poorly paid-445 (66.4%). In the psychometric validation process, the Belimage questionnaire retained the original item structure, and the reliability of the subscales assessed with the Cronbach's alpha coefficient ranged from 0.845 to 0.730. Conclusions The professional image of nurses and midwives varies depending on the profession and the perspective of the assessment in relation to themselves and society. The study showed a particularly unfavorable social image of nurses and midwives, which significantly influences the outlook of nurses and midwives themselves on this issue.